The Implementation of Neurophysiological Pre-Trainin Protocols to Improve Performance, R.O.M and Decrease Pain- A Case Study - Lock, Andrew; Williams, Brogan (British Journal of Healthcare and Medical Research, 2023)
Post-Activation Performance Enhancement (PAPE) is one of many strategies employed to improve athletic performance, modulate pain and improve range of motion (ROM). This neurophysiological pre-training protocol involves physiological mechanisms such as Autogenetic Inhibition, Reciprocal Inhibition (AI & RI), and Post-Activation Potentiation (PAP). A male powerlifter with 20 years of lifting experience presented a primary complaint of right-sided hip pain when attempting to produce leg drive in a competition Bench Press position. The pain was described as a debilitating 9/10 deep hip pain associated with immediate weakness/loss of hip and leg muscle contraction and abandonment of the attempt. The pain was reproducible and exacerbated by hip extension, internal rotation, and abduction, with limited end-range ROM on hip extension. Due to increased pain upon extension, internal rotation, and abduction, a gluteus medius dysfunction and abduction/extension intolerance were differentially diagnosed. Using the PAPE principles, a treatment strategy was designed. In the competition Bench Press, hip extension is recruited to assist with the transmission of Ground Reaction Force (GRF) from the feet, and lower limbs, also to assist with lumbar spine extension optimisation by which an axial skeletal arch is established. Due to the position of the supine body on the bench press board, the femurs are abducted to enable a person to lie supine with the feet on the floor. When under load, the athlete actively extends the hip, with concurrent femoral abduction. This is a high-performance technique. Prior to setting up on the bench press, the participant was instructed to perform six total sets of seated adduction maximum isometric holds against a foam roller between the knees for 10-20 seconds. After the first six rounds of seated adductor isometric holds, the participant reported 0/10 pain on the subsequent warm-up sets. Full ROM was also reported. The participant proceeded to perform a 220kg 1RM Bench Press with the necessary ROM, leg drive, and no pain. The exercise prescription in this study specifically utilised the mechanisms associated with PAPE, PAP, and RI. The aim of this intervention was to activate the adductor musculature to provide hip extension and inhibit abduction activity. The pre-activation sets of maximal isometric adductor holds were specifically designed to elicit a Reciprocal Inhibition of the hip abductors. This provided a neurophysiological window for the subject to reenter hip extension and obtain the optimal Bench Press setup for performance. Further research focussing on neurophysiological rehabilitative strategies should be conducted. This case study provides a great insight into the possibilities and warrants further investigation around the protocols and mechanisms examined above.